2009
DOI: 10.1161/circulationaha.108.821736
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Types of Exercise Training Followed by Detraining on Endothelium-Dependent Dilation in Patients With Recent Myocardial Infarction

Abstract: Background-In coronary artery disease, exercise training (ET) is associated with an improvement in endothelial function, but little is known about the relative effect of different types of training. The purpose of this study was to prospectively evaluate the effect of different types of ET on endothelial function in 209 patients after a first recent acute myocardial infarction. Methods and Results-Endothelial function was evaluated before and after 4 weeks of different types of ET and after 1 month of detraini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
2
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(89 citation statements)
references
References 39 publications
6
75
2
5
Order By: Relevance
“…This strategy could reduce the well-known low compliance of obese children faced with current structured PA programs. 106 The first step low-intensity PA should be considered the needed phase of being more confident with PA, similar to the recommendation suggested for rehabilitation in postmyocardial infarction adults, 107 or for long-term inactivity because of important trauma or fracture. The first-phase PA should be considered a re-education to move.…”
Section: A Multiple-step Strategymentioning
confidence: 99%
“…This strategy could reduce the well-known low compliance of obese children faced with current structured PA programs. 106 The first step low-intensity PA should be considered the needed phase of being more confident with PA, similar to the recommendation suggested for rehabilitation in postmyocardial infarction adults, 107 or for long-term inactivity because of important trauma or fracture. The first-phase PA should be considered a re-education to move.…”
Section: A Multiple-step Strategymentioning
confidence: 99%
“…6) Furthermore, it has been reported that impaired NO-dependent vasodilation is an independent predictive factor of cardiac events in IHD patients. 6) Although other reports found that a few months of aerobic exercise could improve vascular endothelial dysfunction assessed by the conventional method for flow-mediated vasodilation, 7,8) there is little evidence on the influence of stretching exercises.…”
mentioning
confidence: 99%
“…Outros estudos já haviam comprovado uma melhora na função endotelial independente do tipo de treinamento (aeróbio, resistido ou combinado -aeróbio e resistido), do tempo empregado (um mês, três meses ou seis meses) e independente se a execução do treinamento foi realizada com instruções para a realização de exercícios em casa (home-based cardiac rehabilitation) ou se em um centro de reabilitação cardíaca convencional 4,20 . Vona et al 4 relatam que os benefícios na função endotelial vascular periférica adquiridos no treinamento podem ser perdidos em apenas um mês cessado o treinamento.…”
Section: Resultsunclassified
“…Entretanto, programas de reabilitação cardíaca são aceitos como uma intervenção terapêutica não farmacológica para o tratamento de pacientes após infarto agudo do miocárdio e/ou que foram submetidos à CRM 19 , além de melhorar a função endotelial na circulação coronária 20 e periférica 4,21,22 . Em associação, ambos os tratamentos podem ajudar a diminuir as taxas de morbidade e mortalidade destes pacientes.…”
Section: Discussionunclassified
See 1 more Smart Citation